A quantitative and non-invasive vibrational method to assess bone fracture healing: a clinical case study. Issue 1 (1st January 2021) - Mattei, Lorenza; Di Fonzo, Miriam; Marchetti, Stefano; Di Puccio, Francesca
ABSTRACT: Orthopaedics needs a robust diagnostic tool that can help or even replace traditional radiography in bone healing assessment, thus reducing patient exposure to ionizing radiation. We used a vibrational method to assess the healing of a complex fracture treated with external fixation, exploiting a quantitative and non-invasive procedure. Callus stiffening was monitored from the time of surgery until the fixator was removed. Our approach overcomes previous limitations and involves a longer period of healing monitoring (about 9 months), very frequent tests (bi-weekly), and the analysis of a single test configuration. The healing process was monitored by analysing the percentage increments of the squared resonant frequencies (SFIs), related to the stiffness variation and the changes in the frequency response functions. The results were validated by X-rays images, and revealed that the most sensitive parameter to quantify the healing was the SFI of the first resonant frequency which increased by about 20% per month during the formation of the woven callus and up to about 50% at the end of healing completion. This study confirms the potential of the vibrational method as an alternative to radiography in fracture healing assessment.